Determinan Sustanability Financial Performance Islamic Bank Wilayah Asia - Ersi Sisdianto; Einde Evana; Komalasari, Agrianti (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2024)
This study aims to analyze the influence of Islamic Corporate Social Responsibility (ICSR), Islamic Corporate Governance (ICG), and Sustainability Reporting on Sustainability Financial Performance in Islamic banks in Asia, specifically in Indonesia, Malaysia, and Brunei Darussalam. A quantitative approach is employed, using dynamic panel regression analysis to examine the relationship between these three factors and the sustainable financial performance of banks. The results of the study indicate that ICSR has a positive and significant impact on Sustainability Financial Performance, whereas ICG, although showing a positive influence, is not significant. Conversely, Sustainability Reporting shows a negative but insignificant influence on sustainable financial performance. This study has several limitations, including its scope, which only covers Islamic banking data from three countries in Asia, potentially limiting the generalizability of the findings to other regions. Additionally, global factors and additional variables such as company size and government policies were not analyzed, which could affect the results. The practical implications of this study highlight the importance for Islamic banks to enhance the implementation of ICSR and ICG to improve their competitiveness and long-term financial stability. The implementation of Sustainability Reporting also needs to be strengthened in order to have a more significant impact on sustainable financial performance.